Analyzing By.U’s #CumaKamuYangBisa Digital PR Campaign in Building Generation Z Brand Awareness on TikTok - Sapta Aprilia; Lelita Azaria Rahmadiva (Universitas Muhammadiyah Surakarta, 2025)
Purpose: Generation Z increasingly perceives brands as symbolic identities rather than mere providers of products or services, pushing telecommunications companies to move beyond price competition and adopt narrative-driven digital PR strategies on platforms such as TikTok. This research investigates the construction of messages in the By.U Provider digital PR campaign #CumaKamuYangBisa on TikTok. It employs Roland Barthes' semiotic framework to analyze its implications for enhancing brand awareness among Generation Z. Methodology: The study adopts a descriptive qualitative approach, applying Barthes' three layers of meaning in semiotic analysis, namely denotation, connotation, and myth. This Research analyze 11 videos from the #CumaKamuYangBisa digital PR campaign published by @by.u account on TikTok in August 2023. The analysis focus on four message elements: message theme, language style, emotional tone, and visual elements. Results: The digital PR campaign shows a progressive message theme that transitioned from product introduction to emotional integration. It employed an authentic language style resonating with Gen Z communication codes, showcased a variety of emotional tones ranging from comedic to dramatic, and maintained visual consistency through a light blue color palette. The application of Barthes' three layers of meaning indicates that the campaign constructs the brand myth of